Dabigatran Suppresses PAR-1/SphK/S1P Activation of Astrocytes in Experimental Autoimmune Encephalomyelitis Model - Chen, Rong; Cao, Xing; Luo, Wenxiu; Yang, Haodi; Luo, Xinya; Yu, Juming; Luo, Jiaming (Frontiers in Molecular Neuroscience, 2020)
Multiple sclerosis is an inflammatory autoimmune disease affecting the central nervous system (CNS) that currently does not have any effective treatment. Experimental autoimmune encephalomyelitis (EAE) is often employed as a model to mimic the clinical manifestations of multiple sclerosis, mainly CNS demyelination. Coagulation is known to participate in crosstalk with inflammation and autoimmunity. We herein explored the correlation between the coagulation cascade and CNS immune diseases in vitro using primary astrocytes isolated from mice and in vivo using a mouse model of EAE. We showed that dabigatran, an oral clinical anti-coagulant drug, suppressed the activation of thrombin-induced astrocytes, and the underlying mechanisms are related to the activity of protease-activated receptor-1 (PAR-1), sphingosine-1-phosphate (S1P), and sphingosine kinases (SphKs). Importantly, dabigatran effectively recovered neurological function, reduced inflammation in the spinal cord, and prevented spinal cord demyelination caused by EAE. We suggest that dabigatran, a specific inhibitor of thrombin, antagonized the effect of thrombin in astrocytes by limiting the activation of PAR-1, in turn downregulating SphK1 and disrupting S1P receptor signaling. These findings reveal critical information with regard to the relationship between coagulation mechanisms and CNS immune diseases, and will contribute to the clinical translation and development of therapeutic strategies against multiple sclerosis.